On War - Clausewitz, Carl Von (General); Translated by Colonel J. J. Graham (Lahore Combine Printers, 1989)
'On War' is the West's premier work on the philosophy of war. Other soldiers before him had written treatises on various military subjects, but none undertook a great philosophical examination of war on the scale of Clausewitz's. 'On War' is considered to be the first modern book of military strategy. This is due mainly to Clausewitz's integration of political, social, and economic issues as some of the most important factors in deciding the outcomes of a war. It is one of the most important treatises on strategy ever written, and continues to be required reading at many military academies.
Introduction and Notes by Colonel F. N. Maude, C.B. (Late R.E)
Keywords: Military art and science -- War -- Strategy